Spectrum of Erythema Nodosum: A case series - Chowdhury , Mohammed Baieas; Tonmoy, Mahmud Un Nabi; Siam, Rafiq Un Nabi; Akter, Benojeer; Hossain, Khondoker Shoaib; Sarker, Gourav Dey; Paul, Nandita; Ahmed, Akhak (Bangladesh Journal of Medicine, 2024)
Erythema nodosum (EN) is a common acute nodular septalpanniculitis, characterized by the sudden onset of erythematous, firm, solid, deep nodules or plaques painful on palpation and mainly localized on extensor surfaces of the legs. The changes resolve without skin ulcerations spontaneously within a few weeks (mean 2–8). Skin symptoms may be associated with arthralgia, fever, and weaknessThese nodules are characterized by a typical histological appearance regardless of the etiology, marked by acute inflammation of the dermo-hypodermic junction and interlobular septa of the hypodermic fat.Erythema nodosum can occur due to a vast number of underlying causes including but not limited to idiopathic, infectious, and a variety of noninfectious causes. Its occurrence is for the clinician a signal for a wider diagnosis and determination of the cause of occurrence of symptoms. Here we discuss 3 cases of EN of different etiologies and was treated accordingly. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 167